Determinants of Sudden Cardiac Death in Adult Patients With Eisenmenger Syndrome. Issue 6 (17th March 2020) - Chiriac, Anca; Riley, David C.; Russell, Matthew; Moore, Jeremy P.; Padmanabhan, Deepak; Hodge, David O.; Spiegel, Matthew R.; Vargas, Emily R.; Phillips, Sabrina D.; Ammash, Naser M.; Madhavan, Malini; Asirvatham, Samuel J.; et al.
Abstract : Background: Patients with Eisenmenger syndrome are known to have a high incidence of sudden cardiac death (SCD), yet the underlying causes are not well understood. We sought to define the predictors of SCD in this population. Methods and Results: A retrospective analysis of all patients with Eisenmenger syndrome from 2 large tertiary referral centers was performed. ECGs, prolonged ambulatory recordings, echocardiograms, and clinical histories were reviewed; and the cause of death was identified. A total of 246 patients (85 [34.6%] men) with a mean age of 37.3 (±14.2) years were followed up for a median of 7 years. Over the study period, 136 patients died, with 40 experiencing SCD and 74 experiencing cardiac death (sudden and nonsudden). Age, atrial fibrillation, prolonged QRS duration, complete heart block, right atrial enlargement, right bundle branch block, increased right atrial pressure, impaired biventricular function, and the presence of a pacemaker were associated with increased risk of SCD, whereas advanced pulmonary hypertension therapies were protective. Atrial fibrillation (11.45‐fold increased risk; P <0.001) and QRS duration ≥120 ms (2.06‐fold increased risk; P =0.034) remained significant predictors of SCD in the multivariate analysis, whereas advanced pulmonary hypertension therapies were strongly protective against SCD ( P <0.001). Conclusions: Atrial arrhythmias, impaired ventricular function, and conduction system disease were associated with increased risk of SCD in this cohort of patients with Eisenmenger syndrome, providing an opportunity for early risk stratification and potential intervention. Clinical heart failure symptoms (New York Heart Association class ≥II) were predictive of increased mortality but not of SCD, suggesting a potential arrhythmic cause behind SCD.